Case report: Mechanical-electric feedback and atrial fibrillation–Revelation from the treatment of a rare atrial fibrillation caused by annular constrictive pericarditis - Yi, Dong; Li, Lei; Han, Min; Qiu, Rujie; Tao, Liang; Liu, Li; Liu, Chengwei (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is one of the most common arrhythmias encountered in clinical practice. The pathophysiological mechanisms responsible for AF development are complex, vary amongst individuals, and are associated with predisposing factors. Here, we report a case of AF caused by annular constrictive pericarditis (ACP) which is extremely rare due to its unusual anatomical form. In this patient, the AF was refractory to multiple antiarrhythmic medications; However, spontaneous conversion to sinus rhythm occurred when the ring encircling the right and left ventricular cavities along the atrioventricular (AV) groove was severed. This suggests that atrial stretch due to atrial enlargement and increased left atrial (LA) pressure may contribute to the initiation and maintenance of AF. This report highlights the importance of careful investigation of rare predisposing factors for AF using non-invasive diagnostic approaches and mechanical-electric feedback (MEF) as a pathophysiological mechanism for AF initiation and maintenance.